PENINGKATAN KESEJAHTERAAN PETANI MELALUI OPTIMALISASI PENGGUNAAN LAHAN KERING DAN PEMANFAATAN WAKTU LUANG DI KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Putu Arimbawa . .; Muh. Aswar Limi . .; Rosmawaty . . (Fakultas Pertanian Universitas Halu Oleo, 2014)
The research objective was to determine and analyze: (1) The combination of land use that can provide optimal revenue for dryland farmers, (2) The amount of free time that has not been utilized by farmers in dryland farming activities in order to improve the income and welfare of dryland farmers. Data analysis used was the analysis of linear programming (Soekartawi, 2002), and revenue analysis. Research results showed that: (1) income from corn farming in the amount of Rp 3,920,109, and income from peanut farming of Rp 5,449,271; (2) the use of land resources for corn and peanut farming was still not optimal. To achieve optimum farming, it was better to grow peanuts rather that corn, with a minimum area of ​​0.249 hectares; and (3) labor used by farmers for the production of corn had an average of 25.58 working days or 162.58 working days per-hectare, and for peanut farming, required 11.22 working days or 218.47 working days per-hectare. The employment rate for corn and peanut farmings was 58%. Farmers still had 42% spare time for peanut farming, and for other farm expansion. Keywords: welfare, dry land, leisure, business productive, income